Survey to Assess the Impact of the COVID-19 Pandemic on Tinnitus Perception - Oğuz Yılmaz; Handan Yaman; Berna Özge Mutlu; Dilara Bayazıt; Serkan Eti; Hasan Demirhan; Yıldırım Ahmet Bayazıt (Gazi Medical Journal)
Objective: This study aimed to evaluate the effect of coronavirus disease-2019 (COVID-19) on the perception of tinnitus in the population. Methods: A web-based Google survey was performed between May and April 2020, and 1895 volunteers answered questions mainly related to demographic data, daily lifestyle during the pandemic, aural problems, and the presence of tinnitus. Participants with tinnitus were further evaluated using a visual analog scale (VAS) and Tinnitus Handicap Inventory (THI). Results: Of 1895 participants, 184 (9.4%) had tinnitus. Of 184 participants with tinnitus, 64.7% had tinnitus onset before the pandemic, whereas 35.3% had tinnitus onset after the pandemic. There was no significant difference between the parameters of the participants who had no tinnitus and those who had tinnitus onset before and after the pandemic (p>0.05). There was no significant difference between the THI results of the participants with tinnitus onset before and after the pandemic (p>0.05). The VAS scores of the participants with tinnitus onset after the pandemic were higher than those of the participants with tinnitus onset after the pandemic (p<0.05). The participants who had a tinnitus onset before the pandemic described alterations in their tinnitus perception as increased, decreased and unchanged tinnitus perception in 28.8%, 13.4% and 57.8%, respectively. Conclusion: Because of this study, we observed that the COVID-19 pandemic did not increase tinnitus and tinnitus-related problems. However, because of the life-threatening risks that come with the pandemic, people may not consider the effects of tinnitus as a primary problem.